Prestiž povolání učitele - Fiala, Jan (Univerzita Karlova, Fakulta sociálních věd, 2016)
Thesis deals with the prestige of the teaching profession. Its main goal is to try to find out how teachers themselves perceive the prestige connected with their profession. The research consisted of in-depth semi-structured interviews with teachers on this issue and their subsequent analysis. It turned out that although teachers occupy on occupational prestige scales regularly top positions within the interviews they spoke about very low prestige connected with their occupation. The thesis also presents and describes in detail the factors based on analysis of interviews which emerged in connection with low self-esteem of teachers in terms of prestige as a major. This mainly concerns the relatively low income and the related lower standard of living, which forces teachers to have a secondary income. Furthermore, the analysis showed that teachers low self-esteem is affected by alleged lower difficulty of faculties of education, difficult assesment of work results and underastimated difficulty of work from the publics point of view. Not forgetting the little influence of educational unions and the lack of professional organizations that defend the interests of teachers. Last but not least, the low self-esteem of teachers is also affected by publics belief that teaching is not professional or highly. Práce se zabývá problematikou prestiže povolání učitele. Hlavním cílem práce je pokusit se zjistit, jak sami učitelé vnímají prestiž spjatou s jejich povoláním. Výzkum spočíval v hloubkových polostrukturovaných rozhovorech s učiteli na toto téma a v jejich následné analýze. Ukázalo se, že ačkoliv učitelé zaujímají v rámci škál prestiže povolání pravidelně přední příčky, při rozhovorech projevovali názor, že prestiž spjatou s jejich povoláním považují za velmi nízkou. Práce dále předkládá a podrobněji popisuje faktory, které se na základě analýzy realizovaných rozhovorů ukázaly v souvislosti s nízkým sebehodnocením učitelů z hlediska prestiže jako hlavní. Jde především o relativně nižší finanční ohodnocení a s tím spjatou nižší životní úroveň, která nutí učitele k vedlejším příjmům. Dále pak z analýzy vyplynulo, že na nízké sebehodnocení učitelů má vliv údajná nižší obtížnost pedagogických fakult, obtížné posuzování výsledků práce a nedoceněnost náročnosti práce ze strany veřejnosti. Opomenout nelze ani malý vliv školských odborů a neexistenci profesních organizací, které by hájily zájmy učitelů. V neposlední řadě má na nízké sebehodnocení učitelů vliv i přesvědčení veřejnosti, že učitelství není odborným a vysoce kvalifikovaným povoláním. V pozadí řady uvedených faktorů pak identifikuji dle mého. Department of Sociology Katedra sociologie Faculty of Social Sciences Fakulta sociálních věd